Epistemologi Hukum Fatwa MUI Kabupaten Lebak tentang Berboncengan dengan Selain Muhrim - H. B. Syafuri (Universitas Islam Negeri Jakarta, 2016)
The Legal Epistemology of Fatwa of MUI Lebak about Getting a Ride (Berboncengan) with Non- Mahram. The method of Islamic lawmaking (istinbath) is the study of the basic sources and the methods of Mujtahids to produce Islamic law, either by using words (lafzh) or meaning approach. Istinbath method with lafzh approach is by searching statement (nash) in the Qur’an and Hadith and using rules of ushûliyyah. On the other hand, istinbath method with meaning approach is by searching legal purposes (maqasid al-shari’ah) and using qiyas. Riding together between men and women not mahram in Islam according to MUI Lebak is forbidden (haram) based on the Qur’an Surah al-Nur verses 30-31 and Surah al-Isra verse 32, Hadith No. Muslim 1280, and sadd al-dzari’ah.DOI: 10.15408/ajis.v16i2.4451